Manajemen Pendidikan Islam dalam Penguatan Spiritual Well-Being Siswa MTsS Darunnajah Sekarputih - Ahmad Danial (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Strengthening students' spiritual well-being is a fundamental dimension in Islamic education, especially amidst the complexity of moral and psychological challenges faced by students today. Madrasahs not only serve as teaching institutions, but are also required to be able to manage education in a planned and sustainable manner to optimally foster students' spiritual quality. This study aims to describe the management of Islamic education in an effort to strengthen students' spiritual well-being at MTsS Darunnajah Sekarputih. The study used a qualitative approach with a case study design. Data collection techniques included in-depth interviews, participant observation, and documentation studies. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that strengthening students' spiritual well-being is implemented through four main aspects, namely: (1) planning an Islamic education program oriented towards students' spiritual development; (2) implementing consistent habits of worship and religious activities in madrasah life; (3) the strategic role of the madrasah principal's leadership and teacher collaboration in building a religious culture; and (4) continuous program evaluation as an effort to improve the quality of students' spiritual development. The implementation of Islamic education management contributes to increasing students' inner peace, awareness of worship, and religious attitudes.